Wang-Ball Polynomials for the Numerical Solution of Singular Ordinary Differential Equations - Ahmed Kherd; Azizan Saaban; Ibrahim Eskander Ibrahim Fadhel (Iraqi Journal of Science, 2021)
This paper presents a new numerical method for the solution of ordinary differential equations (ODE). The linear second-order equations considered herein are solved using operational matrices of Wang-Ball Polynomials. By the improvement of the operational matrix, the singularity of the ODE is removed, hence ensuring that a solution is obtained. In order to show the employability of the method, several problems were considered. The results indicate that the method is suitable to obtain accurate solutions.